Simultaneous Estimation of Residual Solvents (Ethanol, Acetone, Dichloromethane and Ethyl Acetate) in Dosage Form by GC-HS-FID - Kumar Baliyan, Praveen; Singh, R.P.; Arora, Saurabh (Asian Journal of Chemistry, 2010)
A simple and sensitive method for the determination of ethanol, acetone, dichloromethane and ethyl acetate as residual solvent was developed and validated on gas liquid chromatography with headspace sampler fitted with flame ionization detector (GC-HS-FID). The carrier gas was helium and separation was carried out on Elite-624 (30 meter, 0.53 mm ID, 3μm df) capillary column consisting of 6 % cyanopropylphenyl- 94 % dimethyl polysiloxane stationary phase. The retention time for ethanol, acetone, dichloromethane and ethyl acetate were 11.4, 12.7, 14.0 and 16.9 min, respectively.